2019
DOI: 10.1007/s10803-019-03883-8
|View full text |Cite|
|
Sign up to set email alerts
|

Criminal Behavior and School Discipline in Juvenile Justice-Involved Youth with Autism

Abstract: The objective was to delineate the prevalence of criminal behavior and school discipline in juvenile justice-involved youth (JJY) with autism. A sample of 143 JJY with autism was matched to a comparison group of JJY without a special education classification (N = 286). Results showed that JJY with autism committed significantly fewer property crimes. There were no significant differences between JJY with autism and JJY without special educational needs (SEN) with regard to individual school discipline types. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
(75 reference statements)
0
4
0
Order By: Relevance
“… 5* 14. Slaughter et al ( 2019 ) (USA) Criminal behaviour and school discipline in juvenile justice-involved youth with autism. Juvenile justice involved youth (n = 58,678) with and without autism with learning disabilities and other special educational needs identified from criminal case records of juvenile justice-involved youth between 2006 and 2012 in Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“… 5* 14. Slaughter et al ( 2019 ) (USA) Criminal behaviour and school discipline in juvenile justice-involved youth with autism. Juvenile justice involved youth (n = 58,678) with and without autism with learning disabilities and other special educational needs identified from criminal case records of juvenile justice-involved youth between 2006 and 2012 in Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“…Students identified as disabled also experience higher rates of school discipline than their nondisabled peers (American Psychological Association [APA] Zero Tolerance Task Force, 2008; Christle et al, 2005) and specifically experience more exclusionary disciplinary consequences (Slaughter et al, 2019; U.S. Department of Education, 2014).…”
Section: Teaching Notesmentioning
confidence: 99%
“…Research has found that juveniles in correctional facilities have substantially poorer cognitive functioning compared to the general population, with studies often finding that youth in correctional facilities score so low that they qualify as having learning disabilities (Baltodano et al, 2005; Foley, 2001; Lansing et al, 2014). Furthermore, research has also indicated that having a learning disability is the most prevalent type of disability among juvenile offenders in the juvenile correctional facilities (Platt et al, 2006; Quinn et al, 2005; Richards and Ellem, 2019; Slaughter et al, 2019). In fact, studies focusing on detained juveniles in US populations generally find that about 40 % of youth in juvenile correctional facilities have a learning disability, with emotional disturbance being the most frequent designation (Cruise et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%